2014
DOI: 10.1007/s40097-014-0083-4
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of ruthenium nanoparticles synthesized using Gloriosa superba L. leaf extract

Abstract: This work reports an ecofriendly approach for the synthesis of Ruthenium nanoparticles (Ru NPs) using aqueous leaf extract of Gloriosa superba. G. superba contains cholidonic, superbine, colchicine, gloriosol, phytosterils and stigmasterin, which are found to be responsible for the bio-reduction of Ru NPs. The synthesized Ru NPs were characterized using UV-Vis spectroscopy, Fluorescence spectra, FTIR, XRD, SEM and EDX analyses. UV-Vis spectra of the aqueous medium containing Ru NPs showed a gradual decrease of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 21 publications
1
41
0
Order By: Relevance
“…(Streptococcus pneumoniae, Bacillus subtilis) and Gramnegative (G-), (Proteus vulgaris, Escherichia coli) pathogenic bacteria using disk diffusion method [27]. The bacterial strains were grown in nutrient broth at 37°C until the bacterial suspension reached 1.5 9 10 8 CFU/mL.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…(Streptococcus pneumoniae, Bacillus subtilis) and Gramnegative (G-), (Proteus vulgaris, Escherichia coli) pathogenic bacteria using disk diffusion method [27]. The bacterial strains were grown in nutrient broth at 37°C until the bacterial suspension reached 1.5 9 10 8 CFU/mL.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Seed or seedling treatment with Au NPs (62 µg mL −1 ) improved seed germination in Lactuca sativa and Cucumis sativus , Brassica juncea (10 ppm), and Gloriosa superba (1000 µ m ) . Au NP treatments also enhanced plant growth and yield, including the number, area, and chlorophyll and sugar content of leaves, and 10 and 80 µg mL −1 Au NPs promoted antioxidant production and seed germination in Arabidopsis thaliana . These positive effects, however, may be connected with stimulation of biochemical pathways as the response on the low doses of xenobiotics.…”
Section: Np Effects On Plant Growth and Mechanism Of Actionmentioning
confidence: 99%
“…One study found that NPs reached the apoplast and protoplast in the endodermal and stelar cells of the root, but the particles were profusely stuck at the root surface. [ Au NPs 10 ppm Brassica juncea Improved seed germination [142] Au NPs 1000 µm Gloriosa superba Improved seed germination [143] cultivars of rice with various amylose character (low, medium, and high) in the soil applied with 500 mg CeO 2 NPs per kg soil. [114] The grains from CeO 2 NP treatment contained less starch, iron, sulfur, glutelin, prolamin, lauric, and valeric acids.…”
Section: Mechanism Of Inhibitory Effects Of Nps On Plant Growthmentioning
confidence: 99%
“…The use of NPs is considered as a substitute for antibiotics with better efficacy with negligible side effects and for combating bacterial multidrug resistance. The green synthesized metal or metal oxide NPs have potent antibacterial, antifungal as well as antiparasitic activities [72][73][74][75][76] . The toxicity of metal NPs can be analyzed by various in vitro and in vivo studies.…”
Section: Antimicrobial Activity Of Npsmentioning
confidence: 99%